2022
DOI: 10.3390/agronomy12102565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Long-Term Potassium Dosages on Crop Yield and Potassium Use Efficiency in the Maize–Wheat Rotation System

Abstract: Potassium (K) is the second most important plant nutritional element and is used for numerous physiological processes. We established an eight-year experiment comparing the effects of five K fertilization treatments (0, 48, 84, 120 and 156 kg K ha−1) on crop yield, K use efficiency and soil apparent K balance under the maize–wheat rotation system in the North China Plain. The highest maize and wheat yields were achieved in the K120 treatment, increasing by up to 16.7% and 25.1%, respectively. The increase in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Studies in three long-term fertilisation experiments on agricultural crops in Rothamsted, Bad Lauchstädt, and Skierniewice also showed that the effectiveness of potassium fertilisers decreased when plants experienced deficiencies in nitrogen, phosphorus, and magnesium [42]. Studies in China showed that the most effective rate of potassium fertiliser applied to agricultural crops was 120 kg ha −1 , which increased maize and winter wheat yields by 16.7 and 25.1%, respectively [32]. It is also noted that potassium, like phosphorus, is very important for nitrogen uptake by agricultural plants.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies in three long-term fertilisation experiments on agricultural crops in Rothamsted, Bad Lauchstädt, and Skierniewice also showed that the effectiveness of potassium fertilisers decreased when plants experienced deficiencies in nitrogen, phosphorus, and magnesium [42]. Studies in China showed that the most effective rate of potassium fertiliser applied to agricultural crops was 120 kg ha −1 , which increased maize and winter wheat yields by 16.7 and 25.1%, respectively [32]. It is also noted that potassium, like phosphorus, is very important for nitrogen uptake by agricultural plants.…”
Section: Discussionmentioning
confidence: 97%
“…Similar patterns were found in a long-term (8-year) fertilisation experiment in China, where annual application of 48 kg ha −1 of potassium resulted in 39.5% uptake by plants. However, when the rate of potassium fertiliser application was increased to 156 kg ha −1 , the uptake of potassium decreased to 16.4% [32]. The efficiency of potassium fertiliser use can be improved by taking into account the plant-available K 2 O content in the soil when fertilising, as studies in the USA have shown that it is not economically viable to fertilise agricultural crops with potassium fertilisers if the plant available K 2 O content in the soil is above the average, as they already have sufficient soil reserves of this plant nutrient [48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nutrient absorption efficiency is an important index for characterizing plant nutrient-absorption ability, and rational fertilization can significantly improve grain nutrient-utilization efficiency [47]. However, once the amount of K applied exceeds the crop requirement, K use efficiency will decline [48]. Crop K absorption efficiency gradually decreases with an increase in K application rate [49], while the appropriate K fertilizer improves root characteristics [50], promotes N absorption and metabolism, increases leaf N concentration [2] and N transfer to ears, and increases N and P absorption efficiency [23].…”
Section: Potassium Application Improves N and K Utilization Efficiencymentioning
confidence: 99%
“…Owing to inadequate fertilizer use, significant increase in crop yield (depleting soil solution K), and depletion of K in the soil system, large quantities of K in the soil occur in a fixed form (non-available to plants indirectly) [6,7]. The rapid K depletion of the soil by high-yielding cultivars in intensive crop cultivation systems, coupled with the lack of effective K replacement protocols has induced an escalating K deficiency in soils due to the imbalanced application of fertilizers [8,9].…”
Section: Introductionmentioning
confidence: 99%